STUDY OF THE ANTIBACTERIAL EFFECT OF OCIMUM CAMUM HARVESTED IN BAMAKO AND ITS PERI-URBAN AREA. - Mamadou Traoré; Modibo Diakité; Mantiéré DIARRA; Kadiatou COULIBALY; Chaka Traoré; Brahima SACKO (World Journal of Biology Pharmacy and Health Sciences, 2026)
The overuse of antibiotics against various infections leads to a reduction in their effectiveness. These excesses have led some therapists to return to alternative solutions, in particular so-called gentle medicines, based on the properties of plants and in particular essential oils. Ocimum. Canum is a plant with many therapeutic virtues. This study conducted between August and September in the districts of Sotuba ACI, Daoudabougou, Bakorobabougou, Yirimadio and the village of Mofa (Baguineda) aimed to determine the therapeutic virtues of O. canum in traditional medicine and the effects of its essential oil on E. coli, Salmonella spp and staphylococci. The surveys were conducted among 40 herbalists from 5 markets in Bamako. The Ocimum. canum samples harvested before sunrise were dried in the shade for 7 days. The essential oils from the dried samples were extracted by steam distillation. The results of the surveys showed a frequent use of Ocimum. canum for high blood pressure, malaria, colds and especially for funeral spiritual practices. The yield of the essential oils varied from 1.24 to 1.74%. Biological tests conducted on Escherichia Coli, Salmonella spp and staphylococci showed an effectiveness of these oils on staphylococci at a concentration of 50%.